The complete mitochondrial genome of Hine's emerald dragonfly (Somatochlora hineana Williamson) via NGS sequencing. Issue 2 (3rd July 2018) - Jackson, Craig; McCalla, Sunnie Grace; Amberg, Jon; Soluk, Dan; Britten, Hugh
Abstract: Here, we report the complete mitochondrial genome of the endangered Hine's emerald dragonfly (HED), Somatochlora hineana Williamson. Data were generated via next generation sequencing (NGS) and assembled using a mitochondrial baiting and iterative mapping approach. The full length circular genome is 15, 705 bp with 26.6% GC content. It contains the typical metazoan set of 37 genes: 13 protein-coding genes, 22 transfer RNA (tRNA) and 2 ribosomal RNA (rRNA) genes, and an A + T-rich control region. To our knowledge, this is the first report of the complete HED mitogenome.